Brazil as Horizon: a Productive Transformation Proposal for Colombia - Ortiz Quevedo, Carlos H.; Salazar, Juan D. (Cuadernos de Administración, 2015)
Under the assumption that countries may follow a process of structural transformation characterized by productive diversification and technological sophistication, the Brazilian economy was taken as a guide to reveal the Colombian sectorial developments that would have greater impact upon its intersectoral economic integration. To achieve this, an input-output matrix was constructed for each country with 35 comparable economic sectors. This implies sectorial aggregation work that bears in mind the methodologies of the national accounts of each country. With these comparable matrices, it can be deducted which economic sectors would increase most the intersectoral linkages of Colombia (and the density of the input-output matrix of Colombia). This analysis is important because, according to some structuralist analyses, the density of a country’s network of intersectoral linkages is directly related to its level of income (effect of level) and its economic dynamics (effect of growth)